Aging Alters the Formation and Functionality of Signaling Microdomains Between L-type Calcium Channels and β2-Adrenergic Receptors in Cardiac Pacemaker Cells - Choi, Sabrina; Vivas, Oscar; Baudot, Matthias; Moreno, Claudia M. (Frontiers in Physiology, 2022)
Heart rate is accelerated to match physiological demands through the action of noradrenaline on the cardiac pacemaker. Noradrenaline is released from sympathetic terminals and activates β1- and β2- adrenergic receptors (ΑRs) located at the plasma membrane of pacemaker cells. L-type calcium channels are one of the main downstream targets potentiated by the activation of β-ARs. For this signaling to occur, L-type calcium channels need to be located in close proximity to β-ARs inside caveolae. Although it is known that aging causes a slowdown of the pacemaker rate and a reduction in the response of pacemaker cells to noradrenaline, there is a lack of in-depth mechanistic insights into these age-associated changes. Here, we show that aging affects the formation and function of adrenergic signaling microdomains inside caveolae. By evaluating the β1 and β2 components of the adrenergic regulation of the L-type calcium current, we show that aging does not alter the regulation mediated by β1-ARs but drastically impairs that mediated by β2-ARs. We studied the integrity of the signaling microdomains formed between L-type calcium channels and β-ARs by combining high-resolution microscopy and proximity ligation assays. We show that consistent with the electrophysiological data, aging decreases the physical association between β2-ARs and L-type calcium channels. Interestingly, this reduction is associated with a decrease in the association of L-type calcium channels with the scaffolding protein AKAP150. Old pacemaker cells also have a reduction in caveolae density and in the association of L-type calcium channels with caveolin-3. Together the age-dependent alterations in caveolar formation and the nano-organization of β2-ARs and L-type calcium channels result in a reduced sensitivity of the channels to β2 adrenergic modulation. Our results highlight the importance of these signaling microdomains in maintaining the chronotropic modulation of the heart and also pinpoint the direct impact that aging has on their function.